PENINGKATAN PEMAHAMAN KONSUMSI OBAT IBU HAMIL DI WILAYAH KERJA SIMALUNGUN, SUMATERA UTARA - Rahmawaty Hasan; Burhanudin Gasim Soka; Saidah Saidah (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
Guidelines for medication use during pregnancy must ensure that the therapeutic benefits significantly outweigh any short-term or long-term risks to both the mother and the fetus. This community service activity aimed to improve the understanding of 25 pregnant women in the Pematang Raya area, Simalungun Regency, North Sumatra, regarding the principles of safe medication use during pregnancy. The program applied an educational approach using informational media in the form of posters, combined with material presentation and interactive discussions. The activity began with a pre-test to assess participants’ baseline knowledge about medication use in pregnancy. Following the educational session, a post-test was conducted to evaluate the improvement in understanding. The results indicated a significant increase in knowledge, with 88% of respondents demonstrating a good understanding of safe medication principles during pregnancy. However, further evaluation is necessary for participants who did not fully comprehend the educational material to ensure overall program effectiveness.